EFFECT OF KARAMUNTING LEAF EXTRACT (Melastoma malabathricum) ON THE PROLIFERATION OF BABY HAMSTER KIDNEY-21 (BHK-21) FIBROBLAST CELLS - Aanisah Ramadamayati; Muhammad Yanuar Ichrom Nahzi; Agung Satria Wardhana (Dentino : Jurnal Kedokteran Gigi, 2022)
Background: Pulpitis is an inflammation of dental pulp due to infection of microorganisms from dental caries. Pulpitis is clinically divided into reversible and irreversible pulpitis. Treatment of reversible pulpitis can be done by applying a pulp capping material. The use of calcium hydroxide as a pulp capping material is still not optimal, so an alternative material is needed, namely karamunting leaf (Melastoma malabathricum). The secondary metabolites in karamunting leaf extract have antibacterial activity. Antibacterial activity is needed in the regeneration of pulp tissue. Purpose: To analyze the effect of karamunting leaf extract (Melastoma malabathricum) on viability and proliferation of Baby Hamster Kidney-21 (BHK-21) fibroblast cells using the MTT Assay method. Methods: This study is a purely experimental study with post test only with control group design which were divided into 8 groups. The group was treated with karamunting leaf extract consisted of 5 groups, were 5%, 10%, 15%, 20%, and 25% concentrations also 3 control groups, were positive control (calcium hydroxide), cell control, and media control. Absorbance value was read using ELISA Reader and the percentage of cell viability was calculated. Results: All treatment groups had cell viability values higher than cell control and cause proliferation of BHK-21 fibroblast cells. The One Way Anova showed a value of sig=0,000 (p<0,05), which means that there was a minimum difference in one treatment group. Conclusion: Karamunting leaf extract and calcium hydroxide can maintain viability and cause proliferation of BHK-21 fibroblast cells. Karamunting leaf extract 25% concentration more effective in causing proliferation of BHK-21 fibroblast cells.